2021
DOI: 10.1097/j.pain.0000000000002308
|View full text |Cite
|
Sign up to set email alerts
|

Short-term impact of combining pain neuroscience education with exercise for chronic musculoskeletal pain: a systematic review and meta-analysis

Abstract: Exercise and pain neuroscience education (PNE) have both been used as standalone treatments for chronic musculoskeletal pain. The evidence supporting PNE as an adjunct to exercise therapy is growing but remains unclear. The aim of this systematic review and metaanalysis was to evaluate the effect of combining PNE and exercise for patients with chronic musculoskeletal pain, when compared with exercise alone. A systematic search of electronic databases was conducted from inception to November 6, 2020. A quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 40 publications
2
49
0
5
Order By: Relevance
“…Although several studies have shown that the changes and improvements in functional and symptomatic outcomes with physical therapy and the application of PNE are effective in reducing pain and improving dysfunction [24,25], high-quality studies on PNE and exercise combinations for chronic low back pain are still needed because of the diversity of interventional exercise types, PNE application methods, and participants in previous studies [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have shown that the changes and improvements in functional and symptomatic outcomes with physical therapy and the application of PNE are effective in reducing pain and improving dysfunction [24,25], high-quality studies on PNE and exercise combinations for chronic low back pain are still needed because of the diversity of interventional exercise types, PNE application methods, and participants in previous studies [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Reviews have concluded that exercise therapy vs. usual care offered pain reduction, reduced depression severity, and improved quality of life (11,12). Pain neuroscience education can further enhance these benefits (13).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, PNE is aimed at educating patients on the mechanisms behind chronic pain, highlighting that any credible evidence of danger or safety in body tissues can increase or decrease pain perception, respectively [22], and has been found to be effective in patients with FM [18][19][20][21][22][23][24][25][26][27][28]. It is noteworthy that PNE seems even more effective when it is combined with therapeutic exercise, gradual exposure techniques, and CBT [24,70], all of which are integrated elements in the FIBROWALK program. On the other hand, mindfulness training is aimed at modifying the relationship with one's thoughts-to be more nonjudgmentally open to them, with acceptance-rather than at changing their content [71].…”
Section: Components Of the Fibrowalkmentioning
confidence: 99%